Kemény Zsigmond regényelmélete - Nyilasy , Balázs (Studia Litteraria, 2014)
The paper of Nyilasy deals with Kemény Zsigmond’s essay Ideas on the Novel and the Drama. The author holds the great Hungarian literary man’s essay in high esteem. He finds the Ideas... most remarkable from the standpoint of new cognitive poetics, and outstanding in comparison with the most famous modern essays on cultural philosophy and theory regarding the novel, written by György Lukács, José Ortega Y Gasset, Jürgen Habermas, Michael McKeon. The scholar specifically esteems the main idea of the essay. He analyses Zsigmond Kemény’s endeavour to understand the essence of the novel through the cultural conditions of modernity considering the expectations of the secularized, open-minded citizen-reader; furthermore, how the 19th century literary man anticipates modern approaches of the reception theory and reader-response criticism. It is widely known that outstanding authors of modern novel-theories (Lukács, Ortega and others) treat novel as a genre which expresses uncertainty and the lack of perspective, which so often characterise the twentieth century mind. Zsigmond Kemény considering the main characteristics of the novel also puts centre relativism; uncertainty, yet in comparison with György Lukács, Kemény represents a more moderate, cautious and careful standpoint. In the Ideas about the Novel and the Drama, the appraisal of reflective mind, openness and pluralism show strong presence; however, ‘pantragism’, peculiar characteristic of Lukács’s theory, remains unnoticeable.